Scaffolds for bone restoration from cuttlefish - (:unkn) unknown (ELSEVIER SCIENCE INC, 2005)
Scaffolds of pure hydroxyapatite suitable for either direct clinical use or tissue-engineering applications were successfully produced via hydrothermal transformation of aragonite, obtained from fresh cuttlefish bones, at 200 degrees C followed by sintering. Beyond low production cost, worldwide availability and natural-biological origin of raw materials, the produced scaffolds have ideal pore size and interconnectivity features suitable for supporting biological activities, such as bone tissue growth and vascularization. Bioactivity in vitro tests were excellent: (a) rapid and pronounced formation of hydroxyapatite occurred when the scaffolds were immersed in simulated body fluid (SBF), and (b) outstanding proliferation of osteoblasts was registered. The produced scaffolds can be machined and shaped very easily at any stage of processing. Therefore, these ceramic scaffolds can satisfy both bioactivity demands and the requirements for shaping of tailor-made individualized implants, especially for randomly damaged bones. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: scaffolds; cuttlefish bone; hydroxyapatite; biocompatibility; bioactivity; OSTEOBLAST-LIKE CELLS; BIOACTIVE GLASSES; HYDROXYAPATITE; PROLIFERATION; BIOCERAMICS; TEMPERATURE; COMPOSITES; CULTURE; SYSTEM